Design and Development of an Automatic Parking System Using Card-Based Arduino at Geeta National Plus Junior High School, Cirebon - Nur Ikhwan; Nur Rahmawati; Rismawan (Master of Physics Education Study Programme, 2025)
Card-based automatic parking system is a modern solution to overcome parking problems in urban areas. By utilizing Radio Frequency Identification (RFID) technology and Arduino microcontroller, this system is able to automatically identify vehicles and manage access in and out of the school parking area. This study aims to design and implement an efficient and reliable automatic parking system. The test results show that the system is able to operate with high accuracy in various environmental conditions.